2021
DOI: 10.1007/s00330-020-07677-w
|View full text |Cite
|
Sign up to set email alerts
|

Calcium scoring using virtual non-contrast images from a dual-layer spectral detector CT: comparison to true non-contrast data and evaluation of proportionality factor in a large patient collective

Abstract: Objective Determination of coronary artery calcium scoring (CACS) in non-contrast computed tomography (CT) images has been shown to be an important prognostic factor in coronary artery disease (CAD). The objective of this study was to evaluate the accuracy of CACS from virtual non-contrast (VNC) imaging generated from spectral data in comparison to standard (true) non-contrast (TNC) imaging in a representative patient cohort with clinically approved software. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…The impact of VMI on emphysema quantification has not yet been evaluated. The applicability of VNC imaging was already evaluated in the era of DE-CT 15,48–59 . For PCD-CT, there are hardly any studies dealing with the application of VNC images so far.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of VMI on emphysema quantification has not yet been evaluated. The applicability of VNC imaging was already evaluated in the era of DE-CT 15,48–59 . For PCD-CT, there are hardly any studies dealing with the application of VNC images so far.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other tube-based (rapid tube voltage switch or dual-source) dual-energy CT, it can provide exactly matched high-and low-energy X-ray attenuation, apply material decomposition algorithm in projection domain and not require pre-selection of the scan protocol (10). Some previous studies demonstrated that the VNC images derived from multi-phase contrast scan can replace the non-contrast scan (TNC) (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical routine, both scans are implemented as complementary acquisitions that increase scan time and radiation dose. With the advent of dual-energy and spectral imaging techniques, several studies have evaluated algorithms that allow the estimation of CACS from virtual noncontrast (VNC) images derived from CCTA datasets using material decomposition into 2 materials (soft tissue and iodine) 4–6 . As calcium is represented neither by iodine nor by soft tissue, all of the aforementioned approaches using dual-energy techniques demonstrated a high correlation, but a relevant underestimation of coronary artery calcium (CAC) scores derived from virtual unenhanced images.…”
mentioning
confidence: 99%